Medical adaptive web based tutoring: audiology - Muhammad Sarkawi, Rosalam (2013)
Medical Adaptive Web Based Tutoring: Audiology was develop for medical student enjoying using computers for learning. The main purpose of this Adaptive Web Based Tutoring was developed to facilitate medical students learn more efficient in audiology syllabus. This system is developed using waterfall model approach ADDIE model. Besides that, this project using Adobe Dreamweaver to develop this web tutoring. The adaptation was based on student knowledge. There are three level quiz where students necessary to pass all the level. If student not to pass the level, they can try again. Futhermore, students can read notes slides and explore information about audiology. Students must register information before login into the system.